Multicriteria Modelling on Recycling of Municipal Solid Waste in Subang Jaya - S, Chenayah; P, Agamuthu; E, Takeda (Malaysian Journal of Science, 2007)
Recycling is a relatively new exercise in Malaysia. Even though recycling has been introduced years back, lack of public awareness caused a slowdown in the progress of the recycling exercise. Lack of sufficient recycling facilities or the inappropriateness of the facilities' location contributed further to the slowdown. Presently, about 19,000 tonnes (approaching 20,000 tonnes) of solid waste is being discarded daily. The Ministry of Housing and Local Government sets a recycling goal to be 22% by 2020. The collection rate of recyclables in Subang Jaya is estimated to be 0.43% in 2004. The main purpose of this paper is to study the success of recycling exercise in Subang Jaya, Malaysia. In this paper, to achieve the goal in Subang Jaya, we formulate and analyze various strategies to increase the awareness among the residents and to increase the existing facilities. Evaluating various alternatives inherently involve qualitative criteria and imprecise data. In such cases, the outranking analysis has been frequently used. Therefore, we employ the outranking analysis and use a new exploitation procedure based on eigenvector using the "weighted" in- and out- preference flows of each alternative from outranking relation in a PROMETHEE context.